Analysis of Epididymal Protein Synthesis and Secretion - Zhou, Wei (J Vis Exp, 2018)
The mammalian epididymis generates one of the most complex intraluminal fluids of any endocrine gland in order to support the post-testicular maturation and storage of spermatozoa. Such complexity arises due to the combined secretory and absorptive activity of the lining epithelial cells. Here, we describe the techniques for the analysis of epididymal protein synthesis and secretion by focusing on the model protein family of dynamin (DNM) mechanoenzymes; large GTPases that have the potential to regulate bi-directional membrane trafficking events. For the study of protein expression in epididymal tissue, we describe robust methodology for immunofluorescence labeling of target proteins in paraffin-embedded sections and the subsequent detection of the spatial distribution of these proteins via immunofluorescence microscopy. We also describe optimized methodology for the isolation and characterization of exosome like vesicles, known as epididymosomes, which are secreted into the epididymal lumen to participate in intercellular communication with maturing sperm cells. As a complementary approach, we also describe the immunofluorescence detection of target proteins in an SV40-immortalized mouse caput epididymal epithelial (mECap18) cell line. Moreover, we discuss the utility of the mECap18 cell line as a suitable in vitro model with which to explore the regulation of epididymal secretory activity. For this purpose, we describe the culturing requirements for the maintenance of the mECap18 cell line and the use of selective pharmacological inhibition regimens that are capable of influencing their secretory protein profile. The latter are readily assessed via harvesting of conditioned culture medium, concentration of secreted proteins via trichloroacetic acid/acetone precipitation and their subsequent analysis via SDS-PAGE and immunoblotting. We contend that these combined methods are suitable for the analysis of alternative epididymal protein targets as a prelude to determining their functional role in sperm maturation and/or storage.